Eager - Fox, Helen (New York Wendy Lamb Books, 2004)
Unlike Grumps, their old-fashioned robot, the Bell family's new robot, Eager, is programmed to not merely obey but to question, reason, and exercise free will.
008-012.
A Junior Library Guild selection.
84338
Keywords: Robots -- Fiction; Science fiction